Gut Microbiota Structure and Metabolites, Before and After Treatment in Early Rheumatoid Arthritis Patients: A Pilot Study - Marazzato, Massimiliano; Iannuccelli, Cristina; Guzzo, Maria Paola; Nencioni, Lucia; Lucchino, Bruno; Radocchia, Giulia; Gioia, Chiara; Bonfiglio, Giulia; Neroni, Bruna; Guerrieri, Francesca; Pantanella, Fabrizio; Garzoli, Stefania; et al. (Frontiers in Medicine, 2022)
Rheumatoid Arthritis (RA) is a chronic systemic autoimmune disease. Modifications of gut microbiota seem to be associated with the disease, but the impact of gut microbiota on therapies’ outcome remains unclear. A role of T cells in RA pathogenesis has been addressed, particularly on the Th17/Treg cells balance. Our study aimed to evaluate in early RA (ERA) patients compared to a control group, fecal gut microbiota composition, short-chain fatty acids concentrations, and the levels of circulating Th17/Treg and their own cytokines, before and after three months of standard treatment (Methotrexate (MTX) plus glucocorticoids). Fecal microbiota characterization was carried out on 19 ERA patients and 20 controls matched for sex and age. Significant decreased biodiversity levels, and a partition on the base of the microbiota composition, between the ERA patients at baseline compared to controls, were observed. The co-occurrent analysis of interactions revealed a characteristic clustered structure of the microbial network in controls that is lost in ERA patients where an altered connection between microbes and clinical parameters/metabolites has been reported. Microbial markers such as Acetanaerobacterium elongatum, Cristiansella massiliensis and Gracilibacter thermotolerans resulted significantly enriched in control group while the species Blautia gnavus emerged to be more abundant in ERA patients. Our results showed an alteration in Th17/Treg balance with higher Th17 levels and lower Treg levels in ERA group respect to control at baseline, those data improved after therapy. Treatment administration and the achievement of a low disease activity/remission appear to exert a positive pressure on the structure of intestinal microbiota with the consequent restoration of biodiversity, of the structure of microbial network, and of the abundance of taxa that became closer to those presented by the subject without the disease. We also found an association between Blautia gnavus and ERA patients characterized by a significant reduction of propionic acid level. Furthermore significant differences highlighted at baseline among controls and ERA patients are no more evident after treatment. These data corroborate the role played by gut microbiota in the disease and suggest that therapy aimed to restore gut microbiota would improve treatment outcome.